Development of brain organoid technology derived from iPSC for the neurodegenerative disease modelling: a glance through - Jusop, Amirah Syamimi; Thanaskody, Kalaiselvaan; Tye, Gee Jun; Dass, Sylvia Annabel; Wan Kamarul Zaman, Wan Safwani; Nordin, Fazlina (Frontiers in Molecular Neuroscience, 2023)
Neurodegenerative diseases are adult-onset neurological conditions that are notoriously difficult to model for drug discovery and development because most models are unable to accurately recapitulate pathology in disease-relevant cells, making it extremely difficult to explore the potential mechanisms underlying neurodegenerative diseases. Therefore, alternative models of human or animal cells have been developed to bridge the gap and allow the impact of new therapeutic strategies to be anticipated more accurately by trying to mimic neuronal and glial cell interactions and many more mechanisms. In tandem with the emergence of human-induced pluripotent stem cells which were first generated in 2007, the accessibility to human-induced pluripotent stem cells (hiPSC) derived from patients can be differentiated into disease-relevant neurons, providing an unrivaled platform for in vitro modeling, drug testing, and therapeutic strategy development. The recent development of three-dimensional (3D) brain organoids derived from iPSCs as the best alternative models for the study of the pathological features of neurodegenerative diseases. This review highlights the overview of current iPSC-based disease modeling and recent advances in the development of iPSC models that incorporate neurodegenerative diseases. In addition, a summary of the existing brain organoid-based disease modeling of Alzheimer’s disease was presented. We have also discussed the current methodologies of regional specific brain organoids modeled, its potential applications, emphasizing brain organoids as a promising platform for the modeling of patient-specific diseases, the development of personalized therapies, and contributing to the design of ongoing or future clinical trials on organoid technologies.